Respostas
respondido por:
41
substituindo "x" por "3"
P(3) = 3³ - 3(3)² + 2(3) - 6
P(3) = 27 - 27 + 6 - 6
P(3) = 0
Sim... é raiz!!!
P(3) = 3³ - 3(3)² + 2(3) - 6
P(3) = 27 - 27 + 6 - 6
P(3) = 0
Sim... é raiz!!!
respondido por:
10
p(3) = x³ -3x²+2x -6
P(3) = 3³-3.3²+2.3-6
P(3)=27-3.9+6-6
P(3)= 27-27-0
P(3)= 0
Três é raiz do polinômio,pois P(3) deu igual a 0.
P(3) = 3³-3.3²+2.3-6
P(3)=27-3.9+6-6
P(3)= 27-27-0
P(3)= 0
Três é raiz do polinômio,pois P(3) deu igual a 0.
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás